Recent Advances in Biosensor Technologies for Point-of-Care Urinalysis - Hwang, Chuljin; Lee, Won June; Kim, Su Dong; Park, Sungjun; Kim, Joo Hee (Biosensors, 2022)
Human urine samples are non-invasive, readily available, and contain several components that can provide useful indicators of the health status of patients. Hence, urine is a desirable and important template to aid in the diagnosis of common clinical conditions. Conventional methods such as dipstick tests, urine culture, and urine microscopy are commonly used for urinalysis. Among them, the dipstick test is undoubtedly the most popular owing to its ease of use, low cost, and quick response. Despite these advantages, the dipstick test has limitations in terms of sensitivity, selectivity, reusability, and quantitative evaluation of diseases. Various biosensor technologies give it the potential for being developed into point-of-care (POC) applications by overcoming these limitations of the dipstick test. Here, we present a review of the biosensor technologies available to identify urine-based biomarkers that are typically detected by the dipstick test and discuss the present limitations and challenges that future development for their translation into POC applications for urinalysis.
Keywords: Clinical application; Clinical application for urinalysis; Clinical conditions; Conventional methods; Dipstick test; Health status; Human urine samples; Point of care; Point-of-care urinalysis; Urine sensors; Biomarkers; Biosensing Techniques; Humans; Microscopy; Point-of-Care Systems; Urinalysis; biosensors; clinical application for urinalysis; dipstick test; point-of-care urinalysis; urine sensor